Commercial Quinolone Ear Drops Cause Perforations in Intact Rat Tympanic Membranes. Issue 10 (December 2019) - Dirain, Carolyn O.; Karnani, David N.; Antonelli, Patrick J.
Abstract : Hypothesis: Commercial quinolone ear drops may promote the development of perforations (TMPs) in intact tympanic membrane (TMs). Background: Quinolone ear drops have been associated with TMPs after myringotomy +/- tube placement in a drug-specific manner and potentiation by steroids. Methods: Rats were randomized to six groups (10/group), with one ear receiving otic instillation of dexamethasone, ofloxacin, ciprofloxacin, ofloxacin + dexamethasone, ciprofloxacin + dexamethasone, or neomycin + polymyxin + hydrocortisone—all commercial formulations and at standard clinical concentrations—and the contralateral ear receiving saline, twice daily for 10 days. TMs were assessed over 42 days. Results: No TMPs were seen in ears treated with saline, dexamethasone, or neomycin. At day 10, TMPs were seen in one of 10 ofloxacin- and three of 10 ciprofloxacin + dexamethasone-treated ears ( p = 0.038). At day 14, the ofloxacin TMP healed. In contrast, the three ciprofloxacin + dexamethasone TMPs remained and one new TMP developed in this group. A ciprofloxacin and an ofloxacin + dexamethasone-treated ears also had TMPs ( p = 0.023). By day 21, the ofloxacin + dexamethasone TMP and two of four of the ciprofloxacin + dexamethasone TMPs healed but two new TMPs were seen in ciprofloxacin + dexamethasone ears ( p = 0.0006). At day 28, 1 of 10 ciprofloxacin and 4 of 10 ciprofloxacin + dexamethasone-treated ears had TMPs ( p = 0.0006). By day 35, only one ciprofloxacin + dexamethasone had TMP ( p = 0.42). All TMPS were healed at day 42. Conclusions: Application of commercial quinolone ear drops can cause TMPs in intact TMs. This effect appears to be drug-specific and potentiated by steroids. Abstract : Supplemental Digital Content is available in the text